A Development of Decision Support Systems Selection of Employee Acceptance Using Weighted Product Method - Arief Herdiansah; Nurdiana Handayani; Alfan Kurniawan (Journal of Information System and Informatics, 2019)
Employee selection is an activity to get human resources for a company. Researchers conducted research at PT. Gajah Tunggal Tbk where currently the selection process still uses the conventional method, the current assessment of participants uses technical and non-technical tests with interview methods but at present the company does not yet have a standardized weighting of values tested, so companies sometimes have difficulty determining who should receive from the test participants. Based on the above conditions, researchers conducted decision support system design research using the Weighted Product method to assist companies in getting the right employees according to the employees' technical needs and abilities. Decision support system development refers to the results of data collection using qualitative and quantitative data collection methods. Development of decision support system is built based on the waterfall system development model using the PHP programming language. The system testing method uses the black box method. The design of decision support system from the recruitment selection generator from this study is expected to be a reference for the selection process of employees in similar industries with the place of research conducted by researchers.